Barriers and tools for implementing Nature-based solutions for rail climate change adaptation. (December 2022) - Blackwood, Lorraine; Renaud, Fabrice G.
Abstract: Globally, the need for railways to adapt to the impacts of climate change is increasing rapidly. Nature-based Solutions (NbS) have been identified as potential climate change adaptation (CCA) options for rail infrastructure; however, the limited number of examples of their application on railways highlights that many factors still need to be considered to enable their wider implementation. This study identifies barriers to NbS uptake by the rail industry through a systematic literature review, categorising them into seven key themes, whilst also considering potential tools to facilitate their uptake. The ongoing development of NbS standards and guidance is confirmed as a means to resolve the barriers likely to be faced. A framework to support the uptake of NbS in the rail industry is presented and discussed in the context of the existing literature, with climate change risk assessments being recognised as the entry point for CCA in rail infrastructure management.